2019
DOI: 10.1029/2019gl085613
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of land precipitation to surface evapotranspiration: a nonlocal perspective based on water vapor transport

Abstract: The sensitivity of precipitation over land to surface evapotranspiration (ET) is among the most uncertain issues in land‐atmosphere interactions. Past studies have mostly investigated this issue locally, and it remains a challenge to assess the nonlocal impacts. Here, we use a moisture tracking method and statistical analyses to quantify the sensitivity of precipitation to both local and nonlocal ET. It is found that, in a point‐to‐point sense, boreal summer precipitation is more sensitive to local ET than non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Over certain regions, the uncoupled surface provides enhanced evapotranspiration without soil moisture depletion (since soil moisture is overridden at each time step) leading to the net creation and input of water to the atmosphere. Since the atmosphere cannot store unlimited water, precipitation also increases downstream from the spurious source of evapotranspiration (Berg et al ., 2014; Wei and Dirmeyer, 2019). The evaporative fraction is higher in UNC than in CTL in much of southeastern and eastern South America, including Paraguay, southern Bolivia and eastern Brazil (see Menéndez et al ., 2019, fig.…”
Section: Discussionmentioning
confidence: 99%
“…Over certain regions, the uncoupled surface provides enhanced evapotranspiration without soil moisture depletion (since soil moisture is overridden at each time step) leading to the net creation and input of water to the atmosphere. Since the atmosphere cannot store unlimited water, precipitation also increases downstream from the spurious source of evapotranspiration (Berg et al ., 2014; Wei and Dirmeyer, 2019). The evaporative fraction is higher in UNC than in CTL in much of southeastern and eastern South America, including Paraguay, southern Bolivia and eastern Brazil (see Menéndez et al ., 2019, fig.…”
Section: Discussionmentioning
confidence: 99%
“…A number of recent studies have focused on nonlocal impacts of land surface anomalies, showing, for example, that soil moisture anomalies can exert remote as well as local influences in boreal summer through driving of quasi-stationary Rossby waves and associated circulation anomalies (e.g., Teng et al 2019;Wang et al 2019). In addition, land surface and subsurface temperatures in spring may exert delayed downstream influences on precipitation (Xue et al 2018), and evapotranspiration may remotely influence precipitation over land (Wei and Dirmeyer 2019).…”
Section: E873mentioning
confidence: 99%
“…Yet predictability from land surface states is being harvested only to the extent that land initial conditions and the relevant processes are represented realistically in forecast models (Koster et al 2011;Ardilouze et al 2017). Historically, land surface and atmospheric models are developed separately and their coupled behavior is not calibrated or validated (Dirmeyer et al 2019), so that coupled processes are often not represented accurately (Dirmeyer et al 2018b).…”
Section: E881mentioning
confidence: 99%
“…Using a moisture tracking method Wei and Dirmeyer (2019) found that precipitation in West Africa is sensitive to both local and remote evapotranspiration, while East Africa is mostly driven by local sources of moisture. These previous observation-based findings provide key metrics for assessing CMIP model performance and trustworthiness, as well as, highlighting the need to advance in the understanding of land-atmosphere coupling from a broader perspective that considers both, local and non-local mechanisms, as potential source of coupling changes.…”
Section: Introductionmentioning
confidence: 99%